PERCEPTION OF DIABETIC USERS ABOUT SELF-CARE FOR THEIR FEET: A QUALITATIVE ANALYSIS - Raquel Coelho de Andrade; Hércules Lázaro Morais Campos; Thais Favero Alves; Johrdy Amilton da Costa Braga; Ellem Nara Tananta Dantas; Elisa Brosina de Leon (Universidade Federal do Paraná, 2024)
Objective: To assess the perception of users with type 2 diabetes mellitus (DM2) regarding self-care of their feet using educational videos.  Method: This qualitative study was carried out with users with DM2 treated in primary health care in Amazonas, Brazil. The participants watched two videos on foot care and answered six questions about their perceptions. The data was analyzed using ATLAS.ti 9® software. Results: Three categories were created: 1) 'previous knowledge' with the subcategories 'fragility in professional guidance' and 'videos as tools for remembering'; category 2) 'assimilation of language and audiovisual format'; and category 3) 'possibilities of impact on self-care'. Conclusion: A lack of necessary information on diabetic foot care was observed in remote communities. Audiovisual technologies for health education are essential to inform and promote self-care.